San'ani's View on Women Authority in the Book of Subul al-Salam | ولاية المرأة عند الصنعاني في سبل السلام - Fatihunnada Anis; Ulfa Fauziah (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
At the beginning of the twentieth-century, many discussions arose about the role of women in society or in the social sphere. One characteristic of these discussions is the question "Does Islam allow women to play a role in a society like men?" Some people have seen a saying that the teachings of Islam have caused the decline of Islam and Muslims because of its disagreement with the reality of contemporary society. Some of the teachings of Islam prohibit women from working in the social field in order to leave the education of children which is the supreme interest in religion. And some think that Islam does not close the doors of interest as long as women can have a role such as what men are accustomed to the community as it is in accordance with the teachings of Islam.This research is an answer to the above from the perspective of the Prophet's Hadith by reading the views of the scholars who are familiar with the Prophet's Hadith specifically in the view of al-San'aani in the Book of the Ways of Peace. This research used the objective approach to collect the explanations of the hadiths of the women's authority from the book of the Ways of Peace to the San'ani and compare them with other interpretations of the tradition and modern scholars.This research confirms the study of Tasmin in The Assumption of Women in the Hadith that the textual understanding in the text of hadith will not succeed even if ordered by a woman indicates the prohibition of women in public positions; and Benjamin Bishin in Women, Property Rights, and Islam that close to 90 per cent of Muslim countries deny women equal in leadership; and Shaf'is, Malikis and Hanbalis in general in the judiciary. This research criticizes Zuriatul Khairi studies in Muhammadiyah Theology in marriage with non-believer and Women Leader that Muhammadiyah through historical approach to describe the change of the concept of belief to nash to view how is the relationship between theology and fish and state that religion has no power to deny the leadership of women; and Susan Blackburn in Indonesia, Women and Political Islam that women in Indonesia joined some radical organisation like Permi and PSII in the early twentieth century, and they were slow to find a voice in non-political organisations like NU and Muhammadiyah; and Zulkifli studies in "the concept of the mandate of women comparative study when Nasr Omar Omar and Hussein Mohammed" it allows the mandate of women provided that the efficiency of women in particular the tap and Mohammed al-Ghazali in general.The most important result of this research is that al-Sanani through the book of the ways of peace explained that Al-Maram understood women's conversations using correct methods that women can not take over social affairs from the state or the judiciary and slavery in prayer especially since women suffer from men's disability. Al-Sunani understood the hadith of women in the state verbally and understood the hadeeth of women in prayer iqamah and adhan by the method of hadith contradiction.